Dydaktyka przekładu na studiach filologicznych – ideały, marketing, potrzeby rynku? - Anna Bednarczyk (Ksiegarnia Akademicka Publishing, 2021)
Translation teaching in departments of languages – ideals, marketing, needs of the market?